2021
DOI: 10.5306/wjco.v12.i4.217
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic driver mutations in non-small cell lung cancer: Past, present and future

Abstract: Lung cancer, of which non-small lung cancer is the most common subtype, represents the leading cause of cancer related-death worldwide. It is now recognized that a significant proportion of these patients present alterations in certain genes that drive oncogenesis. In recent years, more of these so-called oncogenic drivers have been identified, and a better understanding of their biology has allowed the development new targeted agents. This review aims to provide an update about the current landscape of driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(101 citation statements)
references
References 126 publications
2
96
0
3
Order By: Relevance
“…The findings of whole-exome sequencing analysis also indicated that EREG expression is induced in oncogenic KRAS-driven PDAs [ 94 ]. Notably, the oncogenic driver mutations, such as EGFR and KRAS, are commonly observed in lung adenocarcinoma [ 95 ]. Moreover, tumor-promoting functions were blocked by anti-EREG antibodies or an EGFR-tyrosine kinase inhibitor (EGFR-TKI, gefitinib or erlotinib) in NSCLC [ 80 ].…”
Section: The Expression Levels Of Ereg During Cancer Progressionmentioning
confidence: 99%
“…The findings of whole-exome sequencing analysis also indicated that EREG expression is induced in oncogenic KRAS-driven PDAs [ 94 ]. Notably, the oncogenic driver mutations, such as EGFR and KRAS, are commonly observed in lung adenocarcinoma [ 95 ]. Moreover, tumor-promoting functions were blocked by anti-EREG antibodies or an EGFR-tyrosine kinase inhibitor (EGFR-TKI, gefitinib or erlotinib) in NSCLC [ 80 ].…”
Section: The Expression Levels Of Ereg During Cancer Progressionmentioning
confidence: 99%
“…In the last two decades, targetable gene alterations have been identified in about 45% of patients with non-small-cell lung cancers (NSCLC) [ 49 ]. In particular, EGFR mutations or ALK-EML4 translocations are identified in up to 50% of non-smokers or Asian patients with NSCLC of the adenocarcinoma histological sub-type [ 50 ].…”
Section: Tyrosine Kinase Inhibitors For the Treatment Of Lung Cancer Brain Metastasesmentioning
confidence: 99%
“…It is well established that certain mutations in critical genes initiate tumorigenesis and confer an invasive phenotype to lung cancer cells. Although a significant portion (~50%) of NSCLCs are linked to mutations in KRAS and EGFR, other implicated genes include BRAF (5%), ALK (3%), MET (3%), and HER2 (3%) [ 7 ]. STK11/LKB1 was first discovered and recognized as an important tumor suppressor gene in the 1990s after analyzing the genomic sequence of patients with Peutz-Jeghers syndrome [ 8 ].…”
Section: Introductionmentioning
confidence: 99%